Pillar[6]arene acts as a biosensor for quantitative detection of a vitamin metabolite in crude biological samples - Masaya Ueno (Nature Portfolio, 2020)
Quick and accurate measurements of specific metabolites are critical to diagnose certain pathological conditions, but quantification methods for relatively low molecular-weight metabolites are limited. Here, the water-soluble pillar[6]arene is used to specifically and quantitatively detect 1-methylnicotinamide in crude urinary samples.